Influencia de la inteligencia emocional en la productividad laboral de Aldeas Infantiles SOS Ibagué (2021)
Emotional intelligence is the ability of the individual to efficiently manage emotions, this ability is made up of feelings, emotional understanding, and the modification of both own and others' emotions. The objective of this research was to determine the influence of emotional intelligence in the field of labor productivity, in this way a search was carried out for investigations related to emotional intelligence and labor productivity, then the MSCEIT and COMPETEA tests were applied. to 25 collaborators of the organization Aldeas SOS, this research was carried out under the analytical empirical paradigm because an emotional intelligence program was designed based on the results obtained, w